(untitled) (Bangladesh Journal of Child Health, 2014)
Introduction: Acute encephalitis is potentially harmful central nervous system (CNS) inflammation usually caused by infections. The diagnosis is difficult to establish and the etiology often remain unclear. It is endemic throughout the year with occasional epidemics in various localities in our country. So this study was carried out to see the clinical and epidemiological background of hospitalized children with encephalitis. Methodology: A retrospective, observational study, conducted in the department of Paediatrics, Chittagong Medical College Hospital (CMCH). The study period was from January 2009 to December 2010. Children with all ages and sex with clinical case definition of encephalitis characterized by new onset of fever (tempareturee380C) or history of fever during present illness along with altered mental status (confusion, disorientation, coma) and/or neurological deficit (focal or diffuse neurological dysfunction or new onset of seizure) were included. Results: A total of 666 cases were analyzed during the study period. The mean age of the children was 3.77 years (SD± 2.9 years), most of the cases (48.5%) were between 12 months to 60 months age group. Urban cases were 144 (25%) & rural cases were 421 (75%).Year wise admissions in 2009 & 2010 were 312 & 354; deaths were 46% & 56%. Prominent clinical features of admitted encephalitis patients were fever (89%), convulsion (84%) and altered consciousness (75%). The trend of admission was high in the months of January, April and October. Significant number of death were observed under 5 years age group (P value <0.02%). Conclusion: It was observed from this study that clinical profiles among children with encephalitis can help to understand the course and epidemiological pattern of the disease. The spectrum of encephalitis can differ from rural to urban area and the months of January, April and October were the peak seasons for encephalitis in south-east region of Bangladesh; probably due to viral surge. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20020 Bangladesh J Child Health 2014; VOL 38 (1) : 5-10